Case study: Preliminary design standard for bus stop in Universiti Malaysia Sabah - Yong, Pooi Chee; Salinah Dullah; Sivakumar Kumaresan; Habibah Ghazali; Aslina Baharum; Siti Jahara Matlan (UniSE Press, 2021)
The design of bus stops can cause various problems for passengers, bus drivers, and other vehicles on the road. Malaysia has not yet developed guidelines as a reference for bus stop design to meet consumer requirements, especially on Malaysia’s university campuses. This study was conducted to propose a preliminary design for the bus stop in Universiti Malaysia Sabah (UMS). By referring to various design guidelines and the principles Universal Design, bus stop preliminary design recommendations for Universiti Malaysia Sabah (UMS) were developed. The proposed guideline provides a general overview of the 7 component physical criteria of the bus stop. This guideline may serve as a critical reference to designers, architects, or developers in building better, user-oriented bus stops in the future. This guideline can provide an important reference for designers, architects, or developers to build better, user-oriented bus stops in the future.